1995
DOI: 10.1029/95gl02241
|View full text |Cite
|
Sign up to set email alerts
|

P‐wave image of the Peninsular Ranges Batholith, southern California

Abstract: We invert earthquake P-wave arrival times to image the 3D distribution of P wave velocities in the Mesozoic Peninsular Ranges batholith and nearby areas in southern California. There is a 3% velocity conwast between the eastern and western Peninsular Ranges at 4 and 20 km depth (west side faster) and a 1 to 1.5% velocity conwast across the San Andreas fault zone (south side faster) in the San Bernardino region at 4 to 14 km depth. The San Andreas velocity contrast is due to the juxtaposition of different rock … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
34
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 14 publications
4
34
0
Order By: Relevance
“…This is the side that has more damaged rock in our geological studies and in the seismic imaging of LEWIS et al (2005). These results are in agreement with regional imaging of MAGISTRALE and SANDERS (1995) and SHAPIRO et al (2005), who show the same sense of velocity contrast in the Anza area and farther to the southeast. The existence of more rock damage on the side of the fault that has faster seismic velocity at seismogenic depth is expected if a material interface controls the preferred propagation direction on the fault.…”
Section: Asymmetry Of Structural Properties In Light Of Velocity Strusupporting
confidence: 80%
“…This is the side that has more damaged rock in our geological studies and in the seismic imaging of LEWIS et al (2005). These results are in agreement with regional imaging of MAGISTRALE and SANDERS (1995) and SHAPIRO et al (2005), who show the same sense of velocity contrast in the Anza area and farther to the southeast. The existence of more rock damage on the side of the fault that has faster seismic velocity at seismogenic depth is expected if a material interface controls the preferred propagation direction on the fault.…”
Section: Asymmetry Of Structural Properties In Light Of Velocity Strusupporting
confidence: 80%
“…This compositional boundary, as suggested by Thomson and Girty (1994) and Schmidt (2000), has provided a mechanical weakness in the crust along which the Mesozoic intra-arc strain was concentrated. Also, Magistrale and Sanders (1995) proposed that Quaternary fault development also has been localized at this discontinuity.…”
Section: Peninsular Ranges Batholithmentioning
confidence: 97%
“…For example, mafi c compositions tend to be more resistant to both brittle and ductile deformation than felsic rock types (Jaeger and Cook, 1979;Rutter and Brodie, 1992). Magistrale and Sanders (1995) suggested that the San Jacinto fault zone developed along part of a compositional boundary or discontinuity within the Peninsular Ranges batholith (Fig. 2).…”
Section: Introductionmentioning
confidence: 99%